General Anesthetic Versus Light Sedation: Effect on Pediatric Endoscopy Wait Times. (2013) - Edwards, Christine; Kapoor, Vikram; Samuel, Christopher; Issenman, Robert; Brill, Herbert
Abstract : BACKGROUND: Wait times are an important measure of health care system effectiveness. There are no studies describing wait times in pediatric gastroenterology for either outpatient visits or endoscopy. Pediatric endoscopy is performed under light sedation or general anesthesia. The latter is hypothesized to be associated with a longer wait time due to practical limits on access to anesthesia in the Canadian health care system. OBJECTIVE: To identify wait time differences according to sedation type and measure adverse clinical outcomes that may arise from increased wait time to endoscopy in pediatric patients. METHODS: The present study was a retrospective review of medical charts of all patients <18 years of age who had been assessed in the pediatric gastroenterology clinic and were scheduled for an elective outpatient endoscopic procedure at McMaster Children's Hospital (Hamilton, Ontario) between January 2006 and December 2007. The primary outcome measure was time between clinic visit and date of endoscopy. Secondary outcome measures included other defined waiting periods and complications while waiting, such as emergency room visits and hospital admissions. RESULTS: The median wait time to procedure was 64 days for general anesthesia patients and 22 days for patients who underwent light sedation (P<0.0001). There was no significant difference between the two groups with regard to the number of emergency room visits or hospital admissions, both pre- and postendoscopy. CONCLUSIONS: Due to the lack of pediatric anesthetic resources, patients who were administered general anesthesia experienced a longer wait time for endoscopy compared with patients who underwent light sedation. This did not result in adverse clinical outcomes in this population.